2023
DOI: 10.1002/cpt.2843
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of FDA and EMA Pregnancy and Lactation Labeling

Abstract: The US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) have robust collaboration and dialogue around the need for data and the inclusion of pregnant and lactating individuals in clinical trials. Despite this collaboration, the two agencies have their own standards for the format and content of labeling for these populations. To understand these differences, the pregnancy and lactation labeling sections for 31 approved drugs were compared, and trends were assessed for use of language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Female physiology evolves during pregnancy, and understanding the impact of these changes on the PK of an active pharmaceutical ingredient (API) is critical to ensure its safety and efficacy for both the pregnant woman and the fetus. However, clinical trials rarely include pregnant women for ethical reasons [ 1 , 2 ], and most drugs administered during pregnancy have not been formally tested in a safe clinical environment [ 3 ]. New methods to investigate API behavior in pregnant populations have been developed, such as in vitro systems or preclinical studies [ 4 , 5 ], but the predictability of these tests is limited, and other approaches are mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…Female physiology evolves during pregnancy, and understanding the impact of these changes on the PK of an active pharmaceutical ingredient (API) is critical to ensure its safety and efficacy for both the pregnant woman and the fetus. However, clinical trials rarely include pregnant women for ethical reasons [ 1 , 2 ], and most drugs administered during pregnancy have not been formally tested in a safe clinical environment [ 3 ]. New methods to investigate API behavior in pregnant populations have been developed, such as in vitro systems or preclinical studies [ 4 , 5 ], but the predictability of these tests is limited, and other approaches are mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…cautious interpretation of federal guidance for “not greater than minimal” risk) [ 4 ]. Moreover, regulatory authorities do not require clinical pregnancy data for marketing approval, mandating only non-clinical data and descriptions of restricted use in specific populations, such as pregnant individuals, in drug labelling [ 5 ]. This cautious approach has resulted in the de-prioritization of data generation in pregnant individuals before marketing approval of antiretroviral agents; consequently, most HIV drug labels include no clinical data regarding use in pregnancy or during lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant and lactating women have been excluded from most clinical trials, hence limited human data as regards safety during pregnancy and breastfeeding. 6 Studies of treatment patterns have shown that patients are inclined to reducing the usage of topical products to avoid presumed damage to the foetus which leads to an increase in the severity of F I G U R E 1 Analysis of leave-on and rinse-off cosmetics for pregnant women based on haptens from the European Baseline Series, Cosmetic and Fragrance series by Chemotechnique, 2023. A total of 160 products have been analysed.…”
Section: Introductionmentioning
confidence: 99%